2022
DOI: 10.3390/ijms231810808
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Risk Factors on Mitochondrial Dysfunction, Neuroinflammation, Protein Misfolding, and Oxidative Stress in the Etiopathogenesis of Parkinson’s Disease

Abstract: As a prevalent progressive neurodegenerative disorder, Parkinson’s disease (PD) is characterized by the neuropathological hallmark of the loss of nigrostriatal dopaminergic (DAergic) innervation and the appearance of Lewy bodies with aggregated α-synuclein. Although several familial forms of PD have been reported to be associated with several gene variants, most cases in nature are sporadic, triggered by a complex interplay of genetic and environmental risk factors. Numerous epidemiological studies during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 306 publications
0
15
0
Order By: Relevance
“…Neuroprotective compounds superimpose over the cyclised ring; fitting points are frequently cyclised ring atoms including O8, with bulky chemical groups ad-jacent to the ring structure. Several neurotoxic pesticides have been linked to the development of Parkinson's through initiating mitochondrial dysfunction [59] and all compounds in Figure 1 Of the simple neurotoxin compounds used in animal models to induce dopaminergic neurodegeneration, MPTP initiates a high proportion of Parkinsonian symptoms [26]. Figure 4 demonstrates that the molecular structures of compounds providing protection against MPTP do not compete for the same template fitting-points; only astilbin has 2 common fitting-points with MPTP.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotective compounds superimpose over the cyclised ring; fitting points are frequently cyclised ring atoms including O8, with bulky chemical groups ad-jacent to the ring structure. Several neurotoxic pesticides have been linked to the development of Parkinson's through initiating mitochondrial dysfunction [59] and all compounds in Figure 1 Of the simple neurotoxin compounds used in animal models to induce dopaminergic neurodegeneration, MPTP initiates a high proportion of Parkinsonian symptoms [26]. Figure 4 demonstrates that the molecular structures of compounds providing protection against MPTP do not compete for the same template fitting-points; only astilbin has 2 common fitting-points with MPTP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, protection of DAergic neurons against deleterious insults and avoidance of neuronal cell death have become an ultimate goal in medicinal research. 5,6 Although, the etiopathogenesis of the disease is still ill defined, several data suggest that exposure to environmental neurotoxicants such as pesticide paraquat (PQ 2+ ) and maneb (MB) 7,8 and genetic susceptibility (e.g., DJ-1 gene 9 ) play an important causative role in mitochondrial dysfunction, protein misfolding, and oxidative stress (OS). In line with this, Mathas and co-workers have recently shown that PQ 2+ and MB inhibited the esterase activity of DJ-1, a critical cellular antioxidant and signaling protein, 10−12 by 20 ± 4 and 100 ± 6%, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The review by Huang et al [ 2 ] addresses the neurotoxic agents that appear to promote the prevalence of Parkinson’s disease. In addition to pesticides and several heavy metals, traumatic brain injury increases the risk of incurring this disorder.…”
mentioning
confidence: 99%